Preparing teachers for the algorithmic educational landscape: A critical mapping of generative AI integration in language teacher education - Karakaya, Kadir; Alpat, Muhammet Furkan; Uçar, Hasan; Karakaya, Özlem; Bozkurt, Aras (Technology in Language Teaching & Learning, 2025)
The increasing integration of generative Artificial Intelligence (AI) tools, such as ChatGPT, in education has prompted growing interest in their pedagogical potential and the emergent competencies required for their effective use in language instruction. While generative AI is beginning to influence language teaching and learning practices, emerging research suggests a growing need to address AI-related literacies and ethical considerations within language teacher education programs. Despite the growing number of studies examining generative AI’s use in language learning contexts, there remains a notable gap in systematically reviewing how generative AI is being addressed in teacher preparation and professional development. To address this gap, this study presents a bibliometric-based systematic literature review of research on generative AI in language teacher education, employing text-mining algorithms, data-mining heuristics, and social network analysis. The findings identify five major thematic clusters in the literature: (1) Professional Development and AI Literacy in Teacher Education, (2) Chatbots and Conversational AI in Language Learning, (3) Generative AI for Instructional Design, Assessment, and Lesson Planning, (4) Generative AI as a Tool for Enhancing EFL Writing Skills, and (5) Exploring Pre-Service Teachers’ Perceptions and Readiness. This review contributes to the growing discourse on AI in education by mapping the current research landscape and identifying critical directions for advancing generative AI integration in language teacher education.